2008
DOI: 10.1073/pnas.0804350105
|View full text |Cite
|
Sign up to set email alerts
|

Spinocerebellar ataxia type 6 knockin mice develop a progressive neuronal dysfunction with age-dependent accumulation of mutant Ca V 2.1 channels

Abstract: Spinocerebellar ataxia type 6 (SCA6) is a neurodegenerative disorder caused by CAG repeat expansions within the voltage-gated calcium (CaV) 2.1 channel gene. It remains controversial whether the mutation exerts neurotoxicity by changing the function of CaV2.1 channel or through a gain-of-function mechanism associated with accumulation of the expanded polyglutamine protein.We generated three strains of knockin (KI) mice carrying normal, expanded, or hyperexpanded CAG repeat tracts in the Cacna1a locus. The mice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
170
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 156 publications
(187 citation statements)
references
References 32 publications
17
170
0
Order By: Relevance
“…We analyzed the formation of NIs in the mutant PCs by immunohistochemistry using an A6RPT-polyQ Ab (10,11). This Ab reacts specifically with humanized Ca v 2.1 and revealed NI formation in the cytoplasm of the Sca6 84Q/84Q Purkinje neurons (10).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We analyzed the formation of NIs in the mutant PCs by immunohistochemistry using an A6RPT-polyQ Ab (10,11). This Ab reacts specifically with humanized Ca v 2.1 and revealed NI formation in the cytoplasm of the Sca6 84Q/84Q Purkinje neurons (10).…”
Section: Resultsmentioning
confidence: 99%
“…Recently, we generated a knockin (KI) mouse model (Sca6 84Q ) carrying an 84 CAG repeat tract in the mouse Cacna1a locus (10). Sca6 84Q mice recapitulate several features of SCA6, including the NI formation in PCs.…”
mentioning
confidence: 99%
“…Studies in recombinant systems expressing CACNA1A cDNA from SCA6 patients suggest that the expanded CAG tract induces a hyperpolarizing shift in channel activation that could produce increased calcium load [45][46][47]. However, studies in Purkinje cells from the SCA6 knock-in mouse model have demonstrated no abnormalities in the intrinsic electrophysiologic properties of mutant Ca V 2.1 [13,48], although it should be noted that these data might not be able to reflect accurately abnormalities in dendritic calcium currents because of technical limitations associated with whole-cell somatic patch clamp recordings.…”
Section: Sca6mentioning
confidence: 99%
“…Studies of these models have yielded a surprising insight: the onset of apparent symptomatic impairment often precedes detectable neuropathology [10][11][12][13][14][15][16][17]. These results suggest that the cell loss observed in patient samples is representative of more advanced disease, and that reduced participation in an affected network due to neuronal loss may not be the only contributor to symptoms observed in patients.…”
Section: Introductionmentioning
confidence: 99%
“…Loss-of-function CACNA1A gene mutants often showed early-onset motor dysfunction associated with distinct alterations of Ca 2+ channel properties, and impaired function of the cerebellar calcium channel Cav2.1 might have a central role in the pathogenesis of certain cases of ataxia (Mori et al, 2000;Wappl et al, 2002). Some types of ataxia, such as spinocerebellar ataxia type 6 were associated with decreased expression or impaired function of CACNA1A protein (Watase et al, 2008). In vivo and in vitro tests herein indicated the decrease in CACNA1A expression upon AgNPs treatment, showing the inhibition of Cav2.1 channel was involved in AgNPs-mediated cerebellar ataxia-like neurobehavior.…”
Section: Discussionmentioning
confidence: 99%